2021
DOI: 10.3389/fonc.2021.732704
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Radiomics Model Incorporating Diffusion-Weighted Imaging and 18F-FDG PET Imaging Improves the Performance of Differentiating Glioblastoma From Solitary Brain Metastases

Abstract: BackgroundThe effectiveness of conventional MRI (cMRI)-based radiomics in differentiating glioblastoma (GBM) from solitary brain metastases (SBM) is not satisfactory enough. Therefore, we aimed to develop an integrated radiomics model to improve the performance of differentiating GBM from SBM.MethodsOne hundred patients with solitary brain tumors (50 with GBM, 50 with SBM) were retrospectively enrolled and randomly assigned to the training set (n = 80) or validation set (n = 20). A total of 4,424 radiomic feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…All studies except one investigated the power of radiomic features arising from MRI for DDx. Only two investigated radiomic features from 18FDG-PET [ 23 , 24 ] and only one investigated the power of CT radiomics for glioma DDx [ 25 ]. A total of 20 studies focused on radiomics for DDx of primary nervous system lymphoma (PCNSL) and glioma (47.6%), with all but one involving IV glioma grade (GBM) patients.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All studies except one investigated the power of radiomic features arising from MRI for DDx. Only two investigated radiomic features from 18FDG-PET [ 23 , 24 ] and only one investigated the power of CT radiomics for glioma DDx [ 25 ]. A total of 20 studies focused on radiomics for DDx of primary nervous system lymphoma (PCNSL) and glioma (47.6%), with all but one involving IV glioma grade (GBM) patients.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 16 studies explored the diagnostic feasibility of radiomic features for DDx of glioma and metastases. All but two of them extracted radiomic features from MRI sequences, while one evaluated features from CT [ 25 ] and one extracted features from PET [ 24 ]. In all but three studies [ 25 , 46 , 58 ], the glioma group consisted of patients with grade IV glioma (GBM).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The AUC was 0.96, and the sensitivity, specificity, and accuracy were 91%, 88%, and 89%, respectively. Zhang et al [11] extracted radiomics features from the MRI and 18 F-FDG PET/CT images of 100 patients with solitary brain tumors (50 GBMs and 50 BM) and used a random forest (RF) classifier to make the prediction. They found that the diagnostic performance of the combined MRI and PET/CT radiomics model (AUC = 0.98) was better than either single radiomics model.…”
Section: Radiomics In the Differential Diagnosis Of Adult Gliomas 21 ...mentioning
confidence: 99%